Head Role School As Inner Motivator Improving Teacher Performance - Andika Aprilianto; M. Ayi Abdul Majid; Ari Kartiko (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
This research was conducted at SMAN 1 Gondang school, with the aim of knowing the role as a motivator and strategy carried out by the principal at SMAN 1 Gondang so that teacher performance increased. The type of research used by the researcher is qualitative research. Subjects in this study included school principals, section head curriculum, and teachers. Researchers collect data using observation, interviews and documentation, for the data wetness technique used is triangulation which includes triangulation of sources, techniques and time. The results of this study indicate that the principal's role as a motivator, among others, creates an emotional connection by making the work environment like a family, being a nurturing parent figure, and also making direct or indirect approaches. Then the strategy carried out by the principal to improve teacher performance, the first is discipline development, discipline is the main factor in achieving success, second is training, continuous efforts to improve the quality of the individual, third is providing motivation, providing stimulus and direction to keep working fully spirit, the fourth is giving awards, as a form of support and attention to teachers who have a good level of performance, the fifth is making a program